2018
DOI: 10.1136/archdischild-2017-314165
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability in the Paediatric Observation Priority Score (POPS)

Abstract: Objective The primary objective of this study was to determine the level of inter-rater reliability between nursing staff for the Paediatric Observation Priority Score (POPS). Design Retrospective observational studySetting Single centre paediatric emergency department Participants 12 participants from a convenience sample of 21 nursing staff.Interventions Participants were shown video footage of three pre-recorded paediatric assessments and asked to record their own POPS for each child. The participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Since the VWS includes main objective vital parameters together with the criterion ‘work of breathing’, we reasoned this would be a more valid score to use. We used an adapted bedside PEWS, since this score was already in use at two of five participating sites and has acceptable inter-rater reliability and usability 18 26 27…”
Section: Discussionmentioning
confidence: 99%
“…Since the VWS includes main objective vital parameters together with the criterion ‘work of breathing’, we reasoned this would be a more valid score to use. We used an adapted bedside PEWS, since this score was already in use at two of five participating sites and has acceptable inter-rater reliability and usability 18 26 27…”
Section: Discussionmentioning
confidence: 99%
“…4 When examined using previously recorded video assessments of children, POPS has been shown to have 'perfect' inter-rater reliability for well children and 'good' inter-rater reliability with an intraclass correlation coefficient (ICC) between 0.66 and 0.74 for unwell children. 5 A subsequent study with a larger sample of children (n=11 videos) and raters (n=46) found a high overall ICC between the raters (95% CI 0.71 to 0.95). 6 On individual components of POPS, the study found high rates of agreement (Fleiss' kappa) for oxygen saturation (over 0.87) and pulse (over 0.76).…”
Section: Original Researchmentioning
confidence: 91%